Pengaruh Senam Ergonomik Terhadap Perubahan Tekanan Darah Pada Lansia Hipertensi Di Wilayah Kerja Puskesmas Jatibaru Kota Bima - Ayatullah, Ayatullah; Wahidah, Wahidah (Barongko: Jurnal Ilmu Kesehatan, 2023)
Hypertension is a cardiovascular problem that often occurs in the elderly. High blood pressure for a long time will cause damage to blood vessels throughout the body, but this can be controlled with pharmacological and non-pharmacological therapies, one of which is by using ergonomic exercises. Ergonomic gymnastics is a gymnastic movement combined with breathing techniques. The purpose of this study was to determine the effect of ergonomic exercise on changes in blood pressure in elderly hypertensives in the Work Area of the Jatibaru Health Center, Bima City. The research design used the Two Group Pre Test- Post Test With Control Group Design. The sampling technique used in this study was purposive sampling with a sample of 30 respondents. There were 15 people in the intervention group and 15 people in the control group. The results of the Wilcoxon signed rank test in the intervention group obtained sig pValue = 0.001 <α 0.05, meaning that there is an effect of ergonomic exercise on changes in blood pressure in the elderly with hypertension. For the results of the Wilcoxon signed rank test in the control group, the value of sig pValue = 0.005 <α 0.05 means that there is an influence in the control group on changes in blood pressure in the elderly with hypertension. The results of the analysis of the Mann Whitney signed test obtained a significance value of pValue = 0.004 <α 0.05.